Didactical Model that Integrates the Student’s Knowledge about Nature and its Effectiveness Analysis - Dzerviniks, Jānis; Poplavskis, Jānis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Nowadays the main goal of science education is to development a competence of nature studies and tehnologies. The relatively low arhievements of Latvian students when compared to the average level of OECD countries, points towards the need to develop the students’ capabilities to use the knowledge and skills acquired in school in real life situations.The authors based upon the theoretical and empirical research developed and approbated a didactical model that integrates the student’s knowledge about nature. This mentioned model forsees a more effective acquisition of physics knowledge, a deeper understanding of physics curriculum, the interaction between nature and technologies, the use of physics knowledge, the development of abilities of scientific enquiries, enrichment of positive emotional attitude, development of expressions of scientific reflexion.